EFL students' epistemic beliefs and their relations to critical thinking and reading achievement - Amatullah, Aidha Azizah; Emaliana, Ive; Junining, Esti (Universitas Muhammadiyah Sidoarjo, 2021)
One of the key points of reading comprehension is epistemic beliefs. Epistemic beliefs can be explained as students’ determination of way of learning. Epistemic beliefs’ relation with critical thinking and reading achievement has not yet been clarified. The study has the aim to explore the relationship between the epistemic beliefs’ of students to their critical thinking and reading achievement. The method of the study is correlational. The participant of the research is 102 students from the 2019 batch of the English Language Education Program of reading comprehension class, A-E class in Universitas Brawijaya. The participants helped to fill the questionnaire. The researcher used SPSS to analyst the questionnaire that has been filled by the participants to know the result of the research. The result of SPSS’s analysis showed that between epistemic beliefs and critical thinking, there is a very strong correlation and between epistemic beliefs and reading achievement, there is a strong correlation. Based on the result of the correlation from SPSS’S analysis, it can be known that there is a close relation between epistemic beliefs, critical thinking, and reading achievement. If the students have high epistemic beliefs, they will have high critical thinking and reading achievement HIGHLISGHTS: Epistemic beliefs are very related to the critical thinking and readingachievement of students. The higher the level of epistemic beliefs, the better the critical thinking ofstudents. The higher the level of epistemic beliefs, the better the reading achievement ofstudents.